2011
DOI: 10.2174/157339911795843140
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Update on the Role of Ghrelin in Glucose Homeostasis

Abstract: Recent evidence highlights an important role of ghrelin in glucose homeostasis. In this review we provide a detailed summary of recent advances in this field. We describe the effects of ghrelin on all aspects of glucose homeostasis including glucose-stimulated insulin secretion, hepatic glucose production and insulin stimulated glucose disposal in the peripheral tissues. The existing evidence suggests ghrelin primarily inhibits insulin release from the pancreas and we highlight an important mechanism involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 66 publications
0
18
0
4
Order By: Relevance
“…The majority of the newly ghrelin-expressing cells are positioned at the periphery of the islet, like alpha cells, but further analysis is required to determine the origin of these cells. Ghrelin is predominantly expressed in the stomach in adulthood and is involved in regulating food intake, hepatic glucose production and preventing glucose disposal in muscle and adipose tissue [46]. The predicted increase in ghrelin production, coupled with the marked reduction in insulin expression, may explain the rapid onset of diabetes in our animals [47].…”
Section: Discussionmentioning
confidence: 90%
“…The majority of the newly ghrelin-expressing cells are positioned at the periphery of the islet, like alpha cells, but further analysis is required to determine the origin of these cells. Ghrelin is predominantly expressed in the stomach in adulthood and is involved in regulating food intake, hepatic glucose production and preventing glucose disposal in muscle and adipose tissue [46]. The predicted increase in ghrelin production, coupled with the marked reduction in insulin expression, may explain the rapid onset of diabetes in our animals [47].…”
Section: Discussionmentioning
confidence: 90%
“…We demonstrated previously that whereas ghrelin gene ablation in wild-type mice has no effect on hyperphagia or obesity, ghrelin ablation in leptin-deficient ob/ob mice ameliorates the diabetic condition (44). Studies have demonstrated that exogenous ghrelin administration inhibits insulin secretion both in vivo and in vitro (4,16,41,44), confirming ghrelin as a negative regulator of insulin secretion and implying that ghrelin has an important role in glucose homeostasis.…”
mentioning
confidence: 82%
“…Numerous studies support a role for ghrelin in blood glucose homeostasis [130, 278, 279]. Glucose homeostasis is regulated by insulin secreted by pancreatic β cells and the insulin responsiveness of peripheral tissues.…”
Section: Physiological Functionsmentioning
confidence: 99%